The effect of work-hardening on the physical work capacity of manual labourers within South African industry - Jacka, Karen-Louise (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1997)
South Africa is a labour-intensive industrially developing country. As a result, in excess of 200 000 workers suffer from musculoskeletal injuries in a year. Research is thus essential to develop more effective strategies in the reduction and rehabilitation of occupational musculoskeletal disorders within industry. It was the hypothesis of this study that by improving the physical work capacity of manual labourers, through participation in an occupation specific work-hardening programme, that the ergonomic stress index and therefore the occurrence of musculoskeletal injuries within industry, may be reduced. Twenty-five male Black and Coloured manual labourers volunteered to participate in this study. In addition to in situ task analyses, the subjects participated in cardiovascular and strength assessments in the laboratory, both pre- and post-participation in the ten-week work-hardening programme. The data were statistically analyzed in order to identify any significant "¢ improvements in the workers' physical work capacity, as measured by cardiovascular, strength and perceptual responses, following the period of work-hardening. Two significant reductions were noted in measures of working heart rate together with significant improvements in grip strength and trunk strength tested at a velocity of 60Â°.secÂ·1 at the post-conditioning assessments. In conclusion, the ten-week work-hardening programme resulted in nominal improvements in all the cardiovascular measures and significant improvements in the subjects' strength performance. However, industrialists must recognise that this study dealt with only one aspect of reducing the ergonomic stress index at the workplace and realise that, in addition to this focus, it remains essential to design the task to fit the human operator.
Keywords: Human engineering; Industrial accidents -- South Africa; Industrial safety -- South Africa; Musculoskeletal system -- Wounds and injuries